The Influence of Purchase Behavior on Purchase Intentions and Purchase Decisions for Processed Apple Products Through E-Commerce - Hasna Luthfiyyan Febriandani; Abdul Wahib Muhaimin; Dwi Retno Andriani (HABITAT, 2021)
During the current pandemic, almost everything we need, both primary and secondary, we can fulfill from online services. In the era of globalization and the ease of online shopping transactions can lead toconsumptive behavior, especially considering the current situation in the corona virus crisis, whereconsumer behavior has begun to change drastically. This study used Structural Equation Modeling-PartialLeast Square (SEM-PLS) analysis with the WarpPLS approach, to predict the magnitude of the relationshipamong latent variables and between latent variable and its indicator. The dominant variables in the researchon the effect of purchase intention of processed apple products at Shopee are trust, online shoppingattitudes, subjective norms and purchase intentions. Trust in product purchase intention produces a pathcoefficient of 0.320 with a confidence interval value [0.160;0.481]. The test results showed that the pathcoefficient was positive with a high significance level. Online shopping attitude on product purchaseintention produces a path coefficient of 0.422 with a confidence interval value [0.261; 0.627], the pathcoefficient was positive with a high significance level so that this sub hypothesis can be accepted.Subjective norm on product purchase intention produces a path coefficient of 0.250 with a confidenceinterval value [0.104;0.397], the path coefficient was positive with a high significance level. Purchaseintention on purchasing decisions produces a path coefficient of 0.509 with a confidence interval value[0.370; 0.648], the path coefficient was positive with a high significance level.